Digital platform-based business models – An exploration of critical success factors - Rohn, Daniel; Bican, Peter; Brem, Alexander; Kraus, Sascha; Clauss, Thomas (Journal of Engineering and Technology Management, 2021)
Recent digital transformation initiatives facilitate the access to platform-based business models on the demand side as well as enabling the necessary proximity to potential customers on the supply side. Due to this network connectivity between people, organizations, resources and entire industries, value and economic growth can be generated within the interactive ecosystem of digital platforms. The special feature of this business model is that competitive advantages, contrary to dominant paradigms, do not primarily rely on the physical infrastructure or the control over scarce and valuable resources. Despite the high practical relevance, little systematic knowledge exists on why platform-based business models often outperform traditional pipeline businesses in many respects. We contribute to this research gap by exploring the critical success factors of platform business models. Based on a qualitative analysis on digital platforms in the metal and steel industry, we identify six key success factors of platform-based business models: We relate these success factors to the design of the three dimensions of business models as described in the literature: (1) value creation, (2) value delivery, and (3) value capture dimensions. Furthermore, our analysis could extend these and design features of the business model by three additional success factors (4) the promotion and sensitization of digital transformation, (5) a suitable platform architecture and strategic judgement of platform providers, as well as (6) the promotion of a start-up culture as central success factors.
CRIS-Team Scopus Importer:2021-05-21
Keywords: Business model; Digital business model; Digitalization; Platform; Qualitative analysis; Steel industry; Success factors